CLAY MINERALS IN SANDSTONE RESERVOIR ROCKS DISTRIBUTION, DIAGENETIC EVOLUTION & POTENTIAL FORMATION DAMAGE - Lejar Yustiningtyas (Jurnal Ilmiah MTG, 2012)
Sandstones are important oil and gas reservoir rocks and most sandstones contain clay minerals. Clay minerals variously occur as detrital (allogenic) particles and grains incorporated in the sediment at the time of deposition or are classified as authigenic minerals (authigenic), which formed at a later stage as cements and replacements within the rock.Kaolinite, chlorite, illite, smectite and mixed layer clays are the most common individual groups of clay minerals present in sandstones. They clays can have complex relationships and appear at various stages in the formation of a rock.Examination of clay minerals in the geological laboratory is undertaken using thin section petrography, scanning electron microscopy (SEM) and X-Ray diffraction (XRD) analyses. This suite of analyses provides an understanding of the types, amounts, distribution and origin of various clays present in a rock, although other types of analysis may also be required in order to provide information on how they will react during oil and gas production.The distribution of clays plays an important role in the ability of the rock to store oil and gas as a reservoir. Clays generally have a negative affect on the reservoir quality of a sandstone, and can block or occlude pores and be the cause of reduced permeability, but some cases the transformation of an unstable mineral, such a feldspar grain, to clay results in formation of additional or secondary pores.It is important to understand the types and distribution of clays when considering oil and gas production. The original sedimentary distribution of clays plays an important role in the distribution and the amount of porosity and permeability, while later stage authigenic clays can often block or occlude pores and ultimately reduce permeability. In certain cases, for instance, authigenic clays may be dislodged within the pore system and will eventually block pores and restrict production, while in other cases certain clays, such as smectite, have the tendency to swell when exposed to water, creating a potential drilling hazard when such clay bearing rock formations are exposed to water-base fluids during drilling, possibly reducing the permeability of a good reservoir rock.Some clays are used in drilling fluids to form an impermeable mud cake to isolate a formation from the invasion of drilling fluid.